ANALYSIS OF THE EFFICIENCY OF USING THE POLYCRYSTALLINE AND AMORPHOUS PV MODULE IN THE TERRITORY OF INDONESIA: In the territory of Indonesia - Susilo, Sugeng Hadi; Asrori, Asrori; Gumono , Gumono (Journal of Applied Engineering Science, 2022)
The article discusses the efficiency analysis of the Photovoltaic (PV) modules, namely polycrystalline and amorphous. The performance in question is the instantaneous efficiency obtained from the measurement of the voltage (V) and current (I) data generated by the two PV modules. In addition, it aims to determine the effect of solar radiation on the output power of polycrystalline and amorphous PV modules. The research was conducted in September 2020, with the outdoor location of the Department of Mechanical Engineering, State Polytechnic of Malang (7,944 °S; 112,613 °E). The independent variables in this study are the current and voltage generated, and the type of PV Module (Polycrystalline and Amorphous). The dependent variable in this study is the actual power and instantaneous efficiency. Measurement of solar radiation using the Glentest SM 206 Solar Power Meter. Measurement of Current and Voltage using a Digital V-I Meter. The results showed that the greater the solar radiation, the higher the actual power and efficiency generated by the PV Module. Polycrystalline PV Modules are capable of producing higher average actual power and average instantaneous efficiency, which are 86.83 W and 11.92% when compared to Amorphous PV Modules, which are 43.88 W and 6.01%.
Keywords: efficiency, photovoltaic module, polycrystalline, amorphous, actual power